Mode of Action of the Bordetella BvgA Protein: Transcriptional Activation and Repression of the Bordetella bronchiseptica bipA Promoter - Mishra, Meenu (American Society for Microbiology, 2005)
The Bordetella BvgAS signal transduction system controls the transition among at least three known phenotypic phases (Bvg(+), Bvg(i), and Bvg(−)) and the expression of a number of genes which have distinct phase-specific expression profiles. This complex regulation of gene expression along the Bvg signaling continuum is best exemplified by the gene bipA, which is expressed at a low level in the Bvg(+) phase, at a maximal level in the Bvg(i) phase, and at undetectable levels in the Bvg(−) phase. The bipA promoter has multiple BvgA binding sites which play distinct regulatory roles. We had previously speculated that the expression profile of bipA is a consequence of the differential occupancy of the various BvgA binding sites as a result of variation in the levels of phosphorylated BvgA (BvgA-P) inside the cell. In this report, we provide in vitro evidence for this model and show that bipA expression is activated at low concentrations of BvgA-P and is repressed at high concentrations. By using independent DNA binding assays, we demonstrate that under activating conditions there is a synergistic effect on the binding of BvgA and RNA polymerase (RNAP), leading to the formation of open complexes at the promoter. We further show that, under in vitro conditions, when bipA transcription is minimal, there is competition between the binding of RNAP and BvgA-P to the bipA promoter. Our results show that the BvgA binding site IR2 plays a central role in mediating this repression.